2000
DOI: 10.2174/1381612003401415
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications for Ligands of Retinoid Receptors

Abstract: Synthetic retinoids, ligands for the RAR and RXR members of the steroid/thyroid superfamily of nuclear hormone receptors, are used for the treatment of psoriasis, acne, photoaging and cancer. Retinoid mechanisms of action for these conditions largely involve effects on epithelial differentiation and modulation of inflammation with some impact on the immune system. Retinoid medicinal chemistry in recent years has identified ligands highly specific for one of the three RAR subtypes (RAR-alpha) and for the RXR fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 147 publications
2
78
0
2
Order By: Relevance
“…To separate the effects of RARγ in the posterior from RARα in the trunk, we characterized RARγ-selective agonist NRX204647 (4647) (Shimono et al, 2011;Thacher et al, 2000) and RARγ-selective inverse agonist NRX205099 (5099) (Tsang et al, 2003) in Xenopus embryos. Like AGN193109, 5099 is an inverse agonist, reducing RARγ signaling activity below basal levels by stabilizing the co-repressor complex bound to RARγ.…”
Section: Rarγ-selective Chemicals Modulate Activation or Repression Bmentioning
confidence: 99%
“…To separate the effects of RARγ in the posterior from RARα in the trunk, we characterized RARγ-selective agonist NRX204647 (4647) (Shimono et al, 2011;Thacher et al, 2000) and RARγ-selective inverse agonist NRX205099 (5099) (Tsang et al, 2003) in Xenopus embryos. Like AGN193109, 5099 is an inverse agonist, reducing RARγ signaling activity below basal levels by stabilizing the co-repressor complex bound to RARγ.…”
Section: Rarγ-selective Chemicals Modulate Activation or Repression Bmentioning
confidence: 99%
“…IFNs are used for treatment of several cancers, including RCC, in addition to viral and neurodegenerative diseases (Kalvakolanu et al, 2001;Cohen and McGovern, 2005). Retinoids are a class of vitamin A metabolites and/or synthetic derivatives, which are used for treatment of several cancers and other disorders (Thacher et al, 2000;Altucci and Gronemeyer, 2001). Previous studies from our lab and those of others showed that the IFN/RA combination synergistically suppresses tumor growth in pre-clinical and clinical settings, compared to the individual agents (Moore et al, 1994;Kalvakolanu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Natural and synthetic derivatives of vitamin A (retinoids) exert profound effects on growth, maturation, and differentiation of many cell types (14), and are currently used in cancer and several dermatological disease therapies (15,16). Retinoids also exhibit putatively beneficial biological actions in the cardiovascular system.…”
mentioning
confidence: 99%